CHOICE OF ANTIPLATELET THERAPY IN VARIOUS PATIENTS WITH ACUTE CORONARY SYNDROMES - E. P. Panchenko («REMEDIUM GROUP» Ltd., 2015)
Despite the high level of cardiology development, cardiovascular diseases remain a major cause of death worldwide. The acute coronary syndrome both with and without ST elevation occupy an increasingly prominent place among them. Dysfunction of the arterialendothelium, chronic inflammation and damage of the atherosclerotic plaque cover, blood flow slowing, and formation of intravascular thrombus underlies various pathogenic forms of ACS. In this regard, the treatment and risk reduction of thrombotic complications of ACS is the main task of the physician in the management of this group of patients. The proposed article discusses optimizing antiplatelet therapy in patients with various ACS forms.